Perceptions of Social Media Use Among U.S. Women Farmers - Kerry Daigle; Sarah Noel Heiss (Journal of Applied Communications, 2021)
Communication networks and knowledge sharing are important for the persistence of small farms that operate outside of industrial agriculture. In past years, internet platforms have been promoted as a tool for farm businesses to connect with customers and other farmers. Social media in particular has gained attention as a user friendly and accessible tool for small business viability. Drawing on Uses and Gratifications Theory, this study uses examines interviews with women farmers' in the United States to explore how they view the role of social media for their agricultural practice. Results demonstrate that women farmers report using social media to reach consumers, seek agricultural information, and maintain emotional connections with other farmers. Though important, women farmers are often overlooked in agricultural research and training programs. Theoretical and practical implications highlight how social media and agricultural trainings can promote media literacy and promote women farmers' success in agriculture.
Keywords: women farmers; social media; farm businesses; uses and gratifications theory